Application of Visual Art Therapy Web Media in Concentration Ability Learning for Autism Children - Sholikhan, Muhammad; Fajrie, Nur; Astuti, Rr Dwi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Autistic children are a term for children who have nervous system disorders that affect their daily behavior. Classification of children's emotions is a pediatric-related treatment that helps identify psychology, as in autistic children. Several models of handling children's emotions have used digital media for the therapeutic use of children with the need for concentration control and learning habits. Art therapy can use technology media to provide treatment through fun and interactive games. The sensation of technology can give space and time for the emotional fulfillment of autistic children. One of the uses of technology that can be used for learning autistic children is through educational website applications. The website’s function provides the right solution to current needs in learning at school, with family, and in the surrounding environment. The material resource facility supports many references and literature using audio-visual media, games, and interactive learning.